(untitled) (Bangladesh Journal of Medical Science, 2024)
Background: Fallopian tube infertility results from sexually transmitted infections and pelvic inflammatory diseases. The most common causes of infertility in women are infections caused by Chlamydia trachomatis and Neisseria gonorrhoeae. These bacterial infections initiate an inflammatory reaction, and ongoing inflammation leads to scarring, obstructing the reproductive tract, and infertility. The pro-inflammatory cytokines IL-6 and TNF-α are involved in the inflammation response triggered by Chlamydia trachomatis and Neisseria gonorrhoeae infections. The study aimed to investigate the connection between the expression of IL-6 and TNF-α in patent and non-patent fallopian tubes. Methods: Analytical observational research with a cross-sectional approach. The 30 subjects were divided into two groups. Group I consisted of 15 subjects diagnosed with non-patent fallopian tubes, and group II consisted of 15 subjects diagnosed with patent fallopian tubes. Sampling technique using consecutive sampling. The research was conducted at Dr. Moewardi General Hospital from January to June 2022. Both groups were assessed based on age, BMI, parity, level of education, occupation, type of infertility, and expression of IL-6 and TNF-α. Results: The expression levels of IL-6 and TNF-α were compared between non-patent and patent fallopian tubes, with statistical analysis indicating a significant difference between the two groups. The p-value for IL-6 was 0.008, and the p-value for TNF-α was 0.030. Conclusion: There was a significant difference in IL-6 expression between the non-patent fallopian tube and the patent fallopian tube, with the IL-6 expression being higher in the non-patent fallopian tube than in the patent fallopian tube. Similarly, the expression of TNF-α on the non-patent fallopian tube and patent fallopian tube shows a higher expression of TNF-α on the non-patent fallopian tube than the patent fallopian tube. Bangladesh Journal of Medical Science Vol. 23 No. 01 January’24 Page : 221-227